LEARNING SOCIETY: IMPLEMENTASI DAN DAMPAK BAGI PEMBANGUNAN PENDIDIKAN ISLAM - Abd. Hafid (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2023)
This research discusses the concept of a learning society and its implementation in the development of Islamic education. The concept of a learning society focuses on changing the mindset and behavior of society obtained through the improvement of education quality and adequate access to education for all segments of society. Recommendations for the development of Islamic education include improving the planning, implementation, and evaluation of Islamic education programs, as well as providing adequate facilities and infrastructure. This research uses a qualitative methodology and employs techniques including literature review, interviews, surveys, and observations. This combination of techniques will help to obtain valid and accurate data and result in conclusions that can be held accountable. The results of this research will ensure the success of Islamic education programs. Overall, the results of this research will make a significant contribution to the development of Islamic education as part of a learning society. This will strengthen and enrich the concepts and strategies for the development of Islamic education, and help to improve the quality and access of education for all segments of society